Effects of Growth Period and Storage Methods on Primary Metabolite Contents and Antioxidant Activities of Morus alba L. Leaf - Lei Hu; Dandan Chen; Wei Zhou; Xiaoyang Chen; Qing Zhang (Molecules, 2022)
(1) Background: Mulberry leaves have been widely consumed due to their richness in bioactive substances and high antioxidant activity. The choice of storage method to ensure the quality of mulberry leaves is a challenge in the supply process. (2) Methods: The differences in primary metabolites of freeze-dried mulberry leaf powder after 30 days of storage under different storage conditions (i.e., vacuum or non-vacuum, 4 °C or room temperature) were investigated. (3) Results: A low temperature and vacuum had better preservation effects on the types and activity of the primary metabolites of mulberry leaves, with vacuum preservation being the best. However, the types of primary metabolites in mulberry leaves were significantly reduced after non-vacuum storage at room temperature compared to those with other storage methods. Among the metabolites detected, including dehydroascorbic acid, various phenolic acids, amino acids, lipids, and carbohydrates showed a significant decrease in their contents of more than 40%, and there was a significant increase in the contents of various compounds of the muconic acid biosynthetic pathway compared to those in other storage methods. Moreover, the antioxidant activity of mulberry leaves stored at room temperature under non-vacuum conditions was also significantly reduced. (4) Conclusions: Vacuum storage is the most ideal storage method for preserving mulberry leaves.